Capacity Building in Africa : The Role of International Financial Institutions - Nsouli, Saleh M. (World Bank, Washington, DC, 2012)
The note looks at the interrelation of three essential components to economic development: capacity building - the development of skills and institutions; good governance; and, economic reform, the two other components which cannot be implemented without well-functioning institutions. It further reviews the rationale and evidence of institutional capacity building, because it provides the framework within which people, and firms participate in the economy. Most importantly, the different specific objectives of international financial institutions are examined, first in their support to investments, e.g., infrastructure and capacity building within an adjustment program; second, in the achievement of economic and social policy; and, third, in encouraging economic development, and business practices, through training, and collaborative efforts. The note specifically reviews the support provided by the International Monetary Fund, which includes capacity building towards enhancing economic expertise, through technical assistance, and training, and, advisory and consulting aid. Effective market-supported institutions of economic management, are indispensable to the economic development process, thus international financial institutions need to formulate approaches to capacity building.